Circulating Levels of Epirubicin Cause Endothelial Senescence While Compromising Metabolic Activity and Vascular Function - Eakin, Amanda J.; Mc Erlain, Tamara; Burke, Aileen; Eaton, Amy; Tipping, Nuala; Allocca, Gloria; Branco, Cristina M. (Frontiers in Cell and Developmental Biology, 2020)
Anthracycline-based chemotherapy is a common treatment for cancer patients. Because it is delivered intravenously, endothelial cells are exposed first and to the highest concentrations, prior to diffusion to target cells. Not surprisingly, vascular dysfunction is a consequence of anthracycline therapy. While chemotherapy-induced endothelial damage at administration sites has been investigated, the effects of lower doses encountered by distant microvascular networks has not. The aim of this study was to investigate the impact of epirubicin, a widely used anthracycline, on healthy endothelial cells to elucidate its effects on microvascular physiology. Here, endothelial cells were briefly exposed to low doses of epirubicin to recapitulate levels in circulation following dilution in the blood and compound half-life in circulation. Both immediate and prolonged responses to treatment were assessed to determine changes in endothelial function. Epirubicin caused a decrease in proliferation and viability in hUVEC, with lower doses resulting in a senescent phenotype in a large proportion of cells, accompanied by a significant increase in pro-inflammatory cytokines and a significant decrease in metabolic activity. Epirubicin exposure also impaired endothelial function with delayed wound closure, reduced angiogenic potential and increased monolayer permeability downstream of VE-cadherin internalization. Primary lung endothelial cells obtained from epirubicin-treated mice similarly demonstrated reduced viability and functional impairment. In vivo, epirubicin treatment resulted in persistent reduction in lung vascular density and significantly increased infiltration of myeloid cells. Modulation of endothelial status and inflammatory tissue microenvironment observed in response to low doses of epirubicin may predict risk for long-term secondary pathologies associated with chemotherapy.